Pengaruh Pemberian Edukasi terhadap Peningkatan Pengetahuan Infeksi Menular Seksual pada Remaja di RT 02/RW 01 Kel. Gates Nan XX - Nur Purnama Sari; Tita Ananta; Intan Silvia Nesva; Rita Gusmaladewi; Hafifa Ramadhani; Lisa Ramadhani; Ramesia Ratnawati (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Sexually Transmitted Infections (STIs) are medical conditions transmitted through sexual contact, including vaginal, anal, and oral intercourse. Knowledge and attitudes regarding STIs among adolescents still require enhancement through early reproductive health education. This initiative aimed to evaluate the effectiveness of health education in improving adolescents' understanding of the dangers and modes of STI transmission. A survey method with a quantitative analytical approach was employed. This community midwifery practice was conducted in RT 02 RW 01, Gates Nan XX Village, involving 16 adolescent respondents. A questionnaire instrument was utilized during data collection to measure the respondents' level of understanding regarding STIs. The results showed that the mean knowledge score before education was 43.21, which subsequently increased to 72.56 following the educational intervention. The paired t-test analysis revealed a significant increase in adolescents' knowledge after receiving the intervention (), indicating that reproductive health education is effective in expanding their understanding of STIs.